2005
DOI: 10.1007/s00280-005-0146-9
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine aerosol: in vitro antitumor activity and deposition imaging for preclinical safety assessment in baboons

Abstract: We have characterized a gemcitabine aerosol suitable for intrathoracic airway deposition and demonstrated that jet nebulization does not alter the cytotoxic properties of the drug. In a primate model, we have developed a scintigraphic procedure for the monitoring of aerosol deposition, and we have demonstrated the safety of nine weekly aerosol administrations of gemcitabine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…Clinical and toxicological studies have been performed by drug aerosolization using this solution for injection in mice, rats, dogs, and baboons. (70)(71)(72)(73)(74) The most important features of these studies can be seen in Table 3.…”
Section: Methotrexatementioning
confidence: 99%
“…Clinical and toxicological studies have been performed by drug aerosolization using this solution for injection in mice, rats, dogs, and baboons. (70)(71)(72)(73)(74) The most important features of these studies can be seen in Table 3.…”
Section: Methotrexatementioning
confidence: 99%
“…Recently, Gagnadoux et al (2005) demonstrated that gemcitabine (GEM) could be administered via endotracheal spray in rats without any marked toxicity at a maximum tolerated dose of 4-6 mg/kg body weight once a week for 9 consecutive weeks. Jet nebulization does not alter the cytotoxic properties of GEM (Gagnadoux et al 2006). Koshkina and Kleinerman (2005) demonstrated that GEM administered via aerosol inhibited the growth of lung metastasis in two osteosarcoma lung metastasis animal models.…”
Section: Introductionmentioning
confidence: 98%
“…A study by Gagnadoux et al showed that the cytotoxicity of a nebulised formulation of the nucleoside analog gemcitabine (GCB) was similar to that of the native drug when tested against NCI-H460 and A549 Non-Small Cell Lung Cancer (NSCLC) cells (Gagnadoux et al, 2006). Another study of the cytotoxicity of a nebulised farnesol formulation containing polysorbate 80 (Tween 80) in vitro for NSCLC lines (H460 and A549) showed that the anticancer properties of nebulised farnesol were essentially the same as those of the native drug (Wang et al, 2003).…”
Section: Pharmacological Properties Of Aerosolised Anticancer Agentsmentioning
confidence: 99%
“…injection (Selting et al, 2008). Gemcitabine was given to 3 baboons via the airways and its concentration in the blood was 25 times lower than after its systemic delivery (Gagnadoux et al, 2006). Dogs with spontaneous pulmonary metastases were given aerosolized paclitaxel and doxorubicin and the drug concentrations in the bloodstream were measured 1 minute later (Hershey et al, 1999).…”
Section: Blood Passagementioning
confidence: 99%